The Effect Of Adding Probiotics In Feed On Maintenance OfHemibagrus nemurusWith Aquaponics Technology - Hakim, Yasir; M. Tang, Usman; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was carried out on June 4 to July 13 2018 which was held at the Regional Technical Implementation Unit Pond of Fisheries and Marine Faculty, Riau University, Pekanbaru.This study aims to determine the addition of the best probiotic doses to the feed in increasing the growth and survival rate of Hemibagrus nemurus with aquaponic technology. The method used in this study is an experimental method using a single-factor completely randomized design with five treatment levels and three replications. The treatments were :1) 0 ml/kg of feed (control), 2) 2 ml/kg of feed, 3) 4 ml/kg of feed, 4) 6 ml/kg of feed and 5) 8 ml/kg of feed.The results of the 40-day study found that the best treatment was 6 ml/kg of feed which gave absolute weight growth of 6.26 g, absolute length growth of 4.12 cm, daily fish growth rate of 1.15%, feed conversion value of 1, 03 and the survival rate of 93.33%. The results of measurements of water quality during the study were temperatures of 25 - 310C, dissolved oxygen from 4.3 to 6.5 mg/L, pH 6-7, ammonia 0.16 - 0.26 mg/L. Keywords: Aquaponics, Hemibagrus nemurus,Probiotics, Growth